Epigenetic Contributions to the Relationship between Cancer and Dietary Intake of Nutrients, Bioactive Food Components, and Environmental Toxicants - Su, L. Joseph; Mahabir, Somdat; Ellison, Gary L.; McGuinn, Laura A.; Reid, Britt C. (Frontiers in Genetics, 2012)
Cancer encompasses a highly heterogeneous group of diseases. It is thought that transition from promotion to progression in carcinogenesis may be driven primarily by epigenetic abnormalities. There is emerging evidence that nutrition and environmental factors affect epigenetic changes. The observation that epigenetic changes are reversible makes them an attractive target for cancer prevention. Until recently, there have been difficulties studying epigenetic mechanisms in interactions between dietary factors and environmental toxicants. The development of the field of cancer epigenetics in the past decade has been rapidly advanced by genome-wide technologies, initially employing microarrays but increasingly high-throughput sequencing, which helped to improve the quality of the analysis, increase the capacity of sample throughput, and reduce the cost of assays. It is particularly true for applications of cancer epigenetics in epidemiologic studies examining the relationship among diet, epigenetics, and cancer because of the issues of tissue heterogeneity, the often limiting amount of DNA samples, and the significant cost of the analyses. This review offers an overview of the state of the science in nutrition, environmental toxicants, epigenetics, and cancer to stimulate further exploration of this important and developing area of science. Additional epidemiologic research is needed to clarify the relationship of these complex epigenetic mechanisms on cancer.